The impacts of traditional homegarden conversion into the commercial one: A case study in Sukapura Village of the Upstream Citarum Watershed, West Java, Indonesia - JULIATI PRIHATINI; JOHAN ISKANDAR; RUHYAT PARTASASMITA; DEDEN NURJAMAN (Biodiversitas Journal of Biological Diversity, 2018)
Prihatini J, Iskandar J, Partasasmita R, Nurjaman D. 2018. The impacts of traditional homegarden conversion into the commercial one: A case study in Sukapura Village of the Upstream Citarum Watershed, West Java, Indonesia. Biodiversitas 19: 1926-1940. In the past, rural homegardens in West Java were planted with various annual and perennial crops. As a result, the vegetation structure of traditional homegardens in rural areas of West Java, Indonesia was very complex, similar to that of forest vegetation. Nowadays, however, due to rapid development of market economic system in rural areas, many traditional homegardens in West Java have been converted into the commercial ones. Consequently, the structure and functions of the homegardens have drastically changed. For example, the vegetation structure has become simpler and dominated by commercial crops, and the gardens serve mostly economic function instead of providing various ecological, socio-economic and cultural functions. The aim of this study was to elucidate: (i) the ecological history of traditional homegardens, (ii) the changes of structure and functions of the homegardens converted from the traditional into the commercial one, and (iii) the positive and negative impacts of conversion of the traditional homegardens into the commercial ones in the Village of Sukapura, the Subdistrict of Kertasari, the District of Bandung, Upstream Citarum Watershed, West Java. The combination of qualitative and quantitative methods were used, while some techniques, including observations, and in-depth interviews with competent informants were applied in this study. The results of study showed that initially the traditional homegardens in Kertasari Village had been predominantly cropped with various annual and perennial crops. However, due to market economic development, the homegardens have been drastically changed. For example, the commercial vegetable crops, including Welsh onion (Allium fistulosum L), carrot (Daucus carota L) and cabbage (Brassica oleracea var capitata) have been predominantly cultivated in the commercial homegardens. Consequently, the household income of the village people who own the commercial homegardens increased, however, some ecological and socio-cultural functions of the commercial homegardens drastically decreased. In addition, some negative impacts of the commercialization of the homegardens have occurred. We suggest that to develop the sustainable village homegardens for the future, the diversity of plants must be maintained to provide ecological function or ecosystem services and the economic production must be improved to increase the income of the rural people.